2009
DOI: 10.1002/chem.200901285
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Substituent Effects on the Activation Energy of Silylene Insertion into Silicon–Chlorine Bonds

Abstract: Insertion reactions of dimethylsilylene (Me(2)Si:) into the silicon-chlorine bond of various substituted chlorosilanes have been computationally studied by using DFT calculations with a 6-31++G(d,p) basis set. All of the insertions investigated herein were exothermic (more than 40 kcal mol(-1)) and proceeded via three-membered cyclic transition states (TS) with one substituent of a chlorosilane in the ring plane and two other substituents out of the plane. Among the two possible concerted insertion pathways, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…354 The effect of the substituents at silicon on the activation energy of insertion was also investigated. 355 Unlike the related reaction of silylenes with the C−Cl bonds (section 2.9), a radical pathway is much less favorable than direct insertion (ΔG ‡ = 44.1 kcal mol −1 for the radical pathway vs ΔG ‡ = 15.3 kcal mol −1 for the direct insertion). Calculations suggest that electron-withdrawing substituents Y in the chlorosilane facilitate the insertion pathway due to the increased interaction between the silylene lone pair and the σ* (Si−Y) orbital while the substituent R mainly exerts a steric effect.…”
Section: Dippmentioning
confidence: 98%
See 1 more Smart Citation
“…354 The effect of the substituents at silicon on the activation energy of insertion was also investigated. 355 Unlike the related reaction of silylenes with the C−Cl bonds (section 2.9), a radical pathway is much less favorable than direct insertion (ΔG ‡ = 44.1 kcal mol −1 for the radical pathway vs ΔG ‡ = 15.3 kcal mol −1 for the direct insertion). Calculations suggest that electron-withdrawing substituents Y in the chlorosilane facilitate the insertion pathway due to the increased interaction between the silylene lone pair and the σ* (Si−Y) orbital while the substituent R mainly exerts a steric effect.…”
Section: Dippmentioning
confidence: 98%
“…Shortly after, Kira et al showed that the isolable silylene 183 oxidatively cleaved the Si–Cl bonds of dichlorodimethylsilane, tetrachlorosilane, and dichlorosilane to give the corresponding 1,2-dichlorodisilanes 465 (Scheme ), whereas reaction with dimethylchlorosilane afforded the Si–H insertion product 466 exclusively. , DFT calculations of the reaction of SiMe 2 with chlorosilanes ClSiYR 2 (R = Me or H; Y = H, Cl, F, Me, or SiH 3 ) revealed stereoelectronic substituent effects, of which the most important is the nucleophilic interaction of the silylene lone pair with the σ* (Si–Y) orbital . The effect of the substituents at silicon on the activation energy of insertion was also investigated . Unlike the related reaction of silylenes with the C–Cl bonds (section ), a radical pathway is much less favorable than direct insertion (Δ G ‡ = 44.1 kcal mol –1 for the radical pathway vs Δ G ‡ = 15.3 kcal mol –1 for the direct insertion).…”
Section: Cleavage Of σ Bondsmentioning
confidence: 99%
“…The insertion reactions of silylene 1 into the Si-Cl bonds of chlorosilanes have been found to occur cleanly [49,50]; hence, the concerted mechanism via three-membered cyclic transition states has been proposed. The mechanism has been supported by the detailed DFT calculations [55][56][57]. Scheme 1.…”
Section: General Proceduresmentioning
confidence: 86%
“…142 The reaction has been shown to evolve through a transition state in which the silylene lone pair approaches the silicon atom of the chlorosilane.…”
Section: Heavy-atom Carbene Analoguesmentioning
confidence: 99%